Desenvolvimento de um modelo para a gestão imobiliária de uma universidade federal - Silva, Rosana Maria Garcia (2021)
The Federal Institutes of Higher Education - IFES have a large amount of real estate properties under their responsibility, which has been expanded due to the Program of Support for the Restructuring and Expansion of Federal Universities - REUNI, the increase of real estate properties being accomplished by means of construction or acquisition of properties. This great amount of properties is used to carry out the activities of teaching, research and science outreach, as well as to provide community services. It is the competence of the managers of these institutions to administrate the properties in order to guarantee that each of them fulfills its social purpose, preventing possible deviations from its aims, seeking to optimize the occupation of each physical space and avoiding, for instance, squandering public resources. Taking this into account, the present research has as its general objective the development of a property management model in the Federal University of Rio Grande do Norte - UFRN. This research is classified as applied, descriptive and with a qualitative approach. The method used in the research is the inductive one. As for the research strategy, it is a case study. The data collection procedures consisted of: bibliographical and documentary research, analysis of records in electronic files, participant observation, semi-structured interview and focus group. Concerning the treatment and the analysis of the data, it was used the technique of content analysis. In this context, the results from data collection procedures, after being correlated with literature review, culminated in the adaptation of the procedure of physical inventory so that it promotes, besides the physical control of real estate properties, a response to the demands for information concerning the real estate property of the institution. As a product of the research, I proposed a model for the management and control of real estate assets within the scope of UFRN.